Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/s0140-6736(16)32616-2
|View full text |Cite|
|
Sign up to set email alerts
|

11 years' follow-up of trastuzumab after adjuvant chemotherapy in HER2-positive early breast cancer: final analysis of the HERceptin Adjuvant (HERA) trial

Abstract: Summary Background Clinical trials have shown that trastuzumab, a recombinant monoclonal antibody against HER2 receptor, significantly improves overall survival and disease-free survival in women with HER2-positive early breast cancer, but long-term follow-up data are needed. We report the results of comparing observation with two durations of trastuzumab treatment at a median follow-up of 11 years, for patients enrolled in the HERA (HERceptin Adjuvant) trial. Methods HERA (BIG 1–01) is an international, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
689
1
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 861 publications
(779 citation statements)
references
References 21 publications
22
689
1
27
Order By: Relevance
“…early breast cancer. 7 Similar results were seen in a combined analysis of data from the North Central Cancer Treatment Group (NCCTG) N9831 Intergroup and National Surgical Adjuvant Breast and Bowel Project (NSABP) B-31 trials, with significantly improved disease-free survival (HR 0.52) at 4 years among patients with operable HER2? disease treated with adjuvant trastuzumab.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…early breast cancer. 7 Similar results were seen in a combined analysis of data from the North Central Cancer Treatment Group (NCCTG) N9831 Intergroup and National Surgical Adjuvant Breast and Bowel Project (NSABP) B-31 trials, with significantly improved disease-free survival (HR 0.52) at 4 years among patients with operable HER2? disease treated with adjuvant trastuzumab.…”
supporting
confidence: 59%
“…cancers, resulting in a notable reduction in disease recurrences. [7][8][9] The Herceptin Adjuvant (HERA) randomized trial showed a significant reduction in risk of a disease-free survival event (hazard ratio [HR] 0.76) and death (0.74) at 11 years of follow-up with the receipt of 1 year of adjuvant trastuzumab compared with observation among 5,099 patients with HER2? early breast cancer.…”
mentioning
confidence: 99%
“…Such a review should assess the quality of model based assessments against established criteria for the production of economic models, heterogeneity in the interpretation of the term "early stage" and seek to identify the source of variation in reported ICERs. Second, some 11 years after the approval for use of Trastuzumab in the treatment of early stage HER2 positive breast cancer, longer term follow up data on cost and survival now exist [77]. A model based analysis that avails of data outside a trial setting with the potential inherent biases this might generate not seems timely.…”
Section: Resultsmentioning
confidence: 99%
“…In most recent clinical trials, the proportion of patients developing symptomatic HF during trastuzumab has been relatively low (0.6% to 3.8%) 27, 30, 31, 32, 33. In fact, the HERA (HERceptin Adjuvant) trial showed an HF incidence of only 0.8% and decreases in LVEF of ≥10% from baseline to an LVEF of <50% in only 7.2% of patients 34.…”
Section: Discussionmentioning
confidence: 99%